Factors affecting home advantage in football World Cup qualification - Pollard, R.; Armatas, V. (International Journal of Performance Analysis in Sport, 2017)
An analysis is made of home advantage in the group stages of qualification for the 2006, 2010 and 2014 football World Cup finals, the first such study of national teams worldwide in a competitive setting. Home advantage was greatest in Africa and South America where the home team won just over 69% of all points earned; it was lowest in Europe (56%). Bolivia was the country with the greatest home advantage. Using each of the 2040 games as the observational units, a general linear model produced a significant fit to the data (R2 = 0.326), home points being the dependent variable, with a set of factors believed to influence home advantage as predictor variables. After controlling for team strength and allowing for the effects of other variables in the model, home points were significantly related to altitude of the home stadium, crowd size and number of time zones crossed by the visiting team (all p < 0.05). There was no significant effect for distance travelled by the away team, the existence of a running track or crowd density. Referees, especially in Africa, issued red cards and awarded penalties against the away team significantly more often than against the home team.